Capacitary type estimates in strongly nonlinear potential theory and applications - Aissaoui, Noureddine (Revista Matemática Complutense, 2001)
In this article a general result on smooth truncation of Riesz and Bessel potentials in Orlicz-Sobolev spaces is given and a capacitary type estimate is presented. We construct also a space of uasicontinuous functions and an alternative characterization of this space and a description of its dual are established. For the Riesz kernel Rm, we prove that operators of strong type (A, A), are also of capacitaries strong and weak types (m, A).